1989
DOI: 10.1111/j.1365-2761.1989.tb00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Aeromonas sobria with mortalities of adult gizzard shad, Dorosoma cepedianum Lesueur

Abstract: This report describes an epizootic in a natural population of spawning females of gizzard shad, Dorosoma cepedianum Lesueur, which occurred in the Potomac River (Maryland, USA). Microbiologieal analysis of moribund shad revealed the presence in pure culture in all the organs examined of one bacterium which was identified as Aeromonas sobria by conventional tube and plate tests. The different API-systems used to attempt for a rapid diagnosis of the disease yielded false negative and positive reactions in import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Segundo Toranzo et al (1989) A adesão bacteriana é um fenômeno de interação célula-superficie, e esta propriedade a faz ideal para as análises em MEV (Knutton, 1995;Ringo et al, 2003). A MEV apresenta a vantagem, ao contrário da microscopia eletrônica de transmissão, de possibilitar o exame mais rápido das bactérias aderentes colonizadoras e de áreas mais extensas da superfície celular (Ringo et al, 2003).…”
Section: Discussionunclassified
“…Segundo Toranzo et al (1989) A adesão bacteriana é um fenômeno de interação célula-superficie, e esta propriedade a faz ideal para as análises em MEV (Knutton, 1995;Ringo et al, 2003). A MEV apresenta a vantagem, ao contrário da microscopia eletrônica de transmissão, de possibilitar o exame mais rápido das bactérias aderentes colonizadoras e de áreas mais extensas da superfície celular (Ringo et al, 2003).…”
Section: Discussionunclassified
“…This was confirmed by our other findings in the brook trout affected on mass in intensive culture, as well as in eel and chub in dam reservoirs. Toranzo et al (1989) found Aeromonas sobria to be associated with outbreaks of fatal disease in gizzard shad (Dorosoma cepedianum) and showed it to be pathogenic to rainbow trout in trhe laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent classification, various species of motile Aeromonas such as A. hydrophila, A. bestiarum, A. sobria, A. jandaei, A. allosaccharophila, A. veronii have been reported as fish pathogens [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%